Conjunctive Relations In Elizabeth Gilbert’s Novel Eat Pray Love Translated Into Indonesian - Zaini Hasan (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This thesis is concerned with the translation field, focusing on conjunctive relation in the process of English-Indonesian translation. Regarding the research methodology, having a focus on content analysis of qualitative method, observation and note taking method are applied for the data collection. The subject matter of the study is the conjunctive relation found in the novel Eat, Pray, and Love by Elizabeth Gilbert and its translation Makan, Doa, dan Cinta applying the theory proposed by Halliday, also involving the occurrence of the eight procedures of translation proposed by Newmark and loss and gain of information proposed by Nida. In relation to the explanation above, it is hoped that by recognizing conjunctive relation and the theory loss and gain of information, the translator will be able to pinpoint and restate meaning more effectively, so that it will be easier to get the intended meanings that want to be translated. Based on the analysis, it is found that all the conjunctive relation types in the data and some of the procedures proposed by Newmark occurs in the novel, and loss and gain of information also occurs in some processes of transferring the message of the conjunctive relation in the SL text into the TL text